THE ROLE OF THE AUDIT COMMITTEE IN PROFIT MANAGEMENT AND FINANCIAL PERFORMANCE TO INCREASE COMPANY VALUE - Ita Nuari Suci Romadhia; Moh. Ubaidillah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
One of the important goals in the establishment of a company is to increase the value of the company. Maximizing the value of the company is very important for every company, especially with the outbreak of the covid 19 virus in Indonesia is currently causing some issuers' shares to fall. This research aims to determine the effect of profit management and financial performance on the value of the company with the audit committee as a moderation variable. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange in 2017-2020 as many as 183 companies. Sampling techniques using purposive sampling that produces 72 manufacturing companies. Data analysis techniques use regression analysis with the SPSS 24 tool. The results of this study showed that profit management had no significant effect on the value of the company, while financial performance had a positive and significant effect on the value of the company. Furthermore, audit committee variables cannot moderate or affect profit management to the value of the company. While the influence of the audit committee on financial performance can strengthen or moderate the value of the company positively and significantly.